Creating better sports schools in Malaysia: A curriculum comparison analysis - Lam, F.E.; Kumarasamy, J.; Johari, M.; Abdul Rani, A.; Mat Rejab, A.S.N. (2008)
Sports play an important role in nation building and brings prestige and glory to the country (Azalina, 2006). In order to produce high performance, the athletes have to go through a proper sports development program and training. The performance of the athletes at junior level highly depends on the Sport School's Comprehensive curriculum implementation. This analysis thus seeks to compare and evaluate the curriculum implemented by four different sports schools in Australia, Singapore, Scotland and United States to ascertain their suitability for implementation in our country. Comparison is also made on various aspects such as funding, teaching staff, facilities, partners and collaborations and many more in running a sports school. From the analysis, it is found that in some of the sports schools, the athletes are not only outstanding in their sports but also in their academic achievement as a result of good planning, clear school vision, mission, aims and the type of curriculum implemented.